"It Took Away the Joy: " First American Mothers' Experiences with Postpartum Depression. Issue 1 (January 2022) - Heck, Jennifer L.; Wilson, Janet Sullivan; Parker, Judy Goforth
Abstract: Background: Postpartum depression (PPD) is a devastating mental illness associated with adverse health outcomes for mother, child, and family. Higher PPD prevalence in First American women suggests a racial/ethnic disparity, yet little is known about how PPD is experienced from their perspective. Purpose: To 1) describe First American women's PPD experiences and the meanings they ascribe to those experiences and 2) describe the cultural knowledge, influences, and practices during the perinatal period. Study Design and Methods: This phenomenological study used a community-based participatory research approach. Criterion and snowball sampling captured First American women who had PPD now or in the past ( N = 8). Interviews used a semistructured guide and thematic analysis followed. Results: Mean age was 30.25 years. Most women were multigravidas ( n = 7) and rated themselves as "very" ( n = 4) or "mostly" (n = 3) Native American. Women were mostly of low socioeconomic status and had a history of depression ( n = 7) and/or a history of prenatal depression ( n = 6). Themes: 1) stressors that contributed to PPD; 2) how PPD made me feel; 3) what made my PPD better; 4) heritage-centered practices; 5) support through PPD; 6) how I felt after PPD; and 7) am I a good mother? Clinical Implications: This study provides a better understanding of some First American women's PPD experiences that facilitates judgment of the importance of PPD within a cultural context. Clinicians need to create culturally appropriate responses to First American women's PPD needs. Abstract : First American women have a disproportionate prevalence of postpartum depression when compared to all women in the United States, but little is known about their perspectives of experiencing this common childbirth complication. In this community-based participatory phenomenological study, First American women describe how it was to have postpartum depression. They were worried about the stigma of postpartum depression and wanted to be 'good mothers." As with other First American women, they relied on their mothers and grandmothers for support. An understanding of cultural norms and practices is an essential aspect of nursing care of women of all ethnic and minoritized groups.